Exploring Brand Attachment in Conjunction with Attachment Styles and Need to Belong - Hood, Elizabeth A.; Berger, Paul D. (Indian Journal of Marketing, 2017)
This paper considered several constructs from both the marketing and psychology areas - brand attachment, attachment theory, and need-to-belong. Attachment theory, in turn, breaks down into secure and insecure attachments, and the latter, in turn, breaks down into anxious attachment and avoidant attachment. The core question addressed is discovering the relationship among these constructs. We developed a questionnaire using established scales of these constructs and took a survey in which a responder picked a brand and indicated his/her attachment to the brand; the other constructs were also measured through this questionnaire. The results indicated that there is a relationship among selected constructs developed for the psychology field, but that no relationship was able to be established between the marketing-area-developed construct of brand attachment and the plausibly related variety of psychology-area-developed constructs.